Management of Environmental Programs for the Arabic Language at Arrayah Sukabumi University - Septia Solihati; Nuril Mufidah; Abdul Malik Karim Amrullah (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2022)
The purpose of this research to describe the planning, organization, implementation and supervision of environmental programs at STIBA AR-RAAYAH. This study uses a qualitative research approach with a case study type of research. The results of this study indicate the following: First: setting daily schedules, creating daily work programmes, weekly work programmes, monthly work programmes, and annual work programmes. Second: in the organization are the Student Department, which includes BEM, the Academic Department, and the Curriculum Department. Third: Monitoring and supervising the process of environmental management of the Arabic language at STIBA AR-RAAYAH by looking at the results of the teacher's work and the results of their education, applying learning strategies/methods and the educational achievements of students, and monitoring student behavior. Fourth: The supporting factors in the formation of the Arabic language environment at Al-Raya University: good beginnings, the process of teaching and learning using the Arabic language, not owning anything that is not related to the Arabic language, native speakers, and housing. Fifth: Obstacle factors in creating the Arabic language environment at Al-Raya University: visitors, employees, non-Arabic lessons, and lecturers outside the university.